HSF1 Protects Sepsis-Induced Acute Lung Injury by Inhibiting NLRP3 Inflammasome Activation - Shi, Xueyan; Li, Tao; Liu, Yanting; Yin, Leijin; Xiao, Lan; Fu, Liyao; Zhu, Yaxi; Chen, Huan; Wang, Kangkai; Xiao, Xianzhong; Zhang, Huali; Tan, Sichuang; et al. (Frontiers in Immunology, 2022)
As an important transcription factor, heat shock factor 1 (HSF1) plays an endogenous anti-inflammation role in the body and can alleviate multiple organ dysfunction caused by sepsis, which contributes to an uncontrolled inflammatory response. The NLRP3 inflammasome is a supramolecular complex that plays key roles in immune surveillance. Inflammation is accomplished by NLRP3 inflammasome activation, which leads to the proteolytic maturation of IL-1β and pyroptosis. However, whether HSF1 is involved in the activation of the NLRP3 inflammasome in septic acute lung injury (ALI) has not been reported. Here, we show that HSF1 suppresses NLRP3 inflammasome activation in transcriptional and post-translational modification levels. HSF1 can repress NLRP3 expression via inhibiting NF-κB phosphorylation. HSF1 can inhibit caspase-1 activation and IL-1β maturation via promoting NLRP3 ubiquitination. Our finding not only elucidates a novel mechanism for HSF1-mediated protection of septic ALI but also identifies new therapeutic targets for septic ALI and related diseases.